Using 5WH Competency Questions for Validating Information Retrieval from Al-Quran: A Methodological Approach - Nazia Nishat; Rosalina Abdul Salam; Yusuf Mahbubul Islam; Zulkifly Mohd Zaki (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Science Health & Technology, Volume 11 Issue 1 Page (132–141)